Knowledge And Preventive Practice Towards Covid-19 Infection Among Pregnant Women In Public Hospitals Addis Ababa, Ethiopia, 2022 - Mezgebu Ashine, Taye; Ejigu Admasu, Roman; Dejene Wolde, Yesuneh; Ali Jemal, Samrawit (Journal of Women's Reproductive Health, 2023)
Background The novel coronavirus COVID-19 has created massive challenges to public health worldwide. Pregnant women are an immune-depressed status which makes pregnant women generally more vulnerable to COVID-19 infection and severe illness. The present preventive measure practices have gaps. Therefore, the current study aimed to present accurate and latest information regarding preventive measures for COVID-19 infection among pregnant women. Methods and materials Institution-based cross-sectional study design was conducted on 422 pregnant women in public hospitals in Addis Ababa using a pretested structured questionnaire. Face-to-face interview on pretested and structured questions was conducted to collect the data between January 12 and February 15, 2022. The collected data were entered into Epi data version 4.4.2.2 and exported to SPSS window version 25 for analysis. Descriptive statics and multivariable logistic regression were analyzed. Odds ratio with a 95% confidence interval and p-value ≤ 0.05 were declared statistical significance independent variables. Result A total of 418 pregnant women participated, and the response rate was 99.05%. About 417 (99.8%) pregnant women reported never hearing about COVID-19. Of those who heard about COVID-19, only 49% and 54.3% had good knowledge and had good practice towards COVID-19 infection respectively. Age (26-30yrs (AOR=0.46, 95%CI: 0.014,0.12), no education (AOR=0.23, 95%CI: 0.099-0.52), Primary school (AOR=0.199, 95%CI: 0.104-0.4) and Secondary school (AOR=0.282, 95%CI: 0.14-0.55), divorced (AOR=0.15, 95%CI: 0.065-0.34) and widowed (AOR=0.16, 95%CI: 0.024-1.03)) were factors that associated with knowledge towards COVID-19 infection. Age (30-35yrs (AOR=0.334, 95%: 0.115-0.97) and >36yrs (AOR=0.28, 95%CI: 0.11-0.69)), no education (AOR=0.06, 95%CI: 0.019-0.18), being a civil servant (AOR= 0.28, 95%CI: 0.122-0.66), divorced (AOR=0.042, 95%CI: 0.01-0.18), having >4 family size (AOR=0.334, 95%CI: 0.169-0.66), no previous complication of pregnancy outcomes (AOR=0.019, 95%CI: 0.01-0.061), chronic health problem (AOR=14.66, 95%CI: 0.457-39.4) and two ANC visit (AOR=5.704, 95%CI: 2.41-13.5) were factors that associated with the practice towards COVID-19. Conclusion In this study area, only half of pregnant women had good knowledge and good practice about covid-19 infection prevention measures.
Keywords: COVID-19; Pregnant women; Infection; Addis Ababa.